HUBUNGAN KARAKTERISTIK IBU, PENGETAHUAN DAN SIKAP DENGAN PERILAKU PERAWATAN PAYUDARA PADA IBU MENYUSUI ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PEGANDAN - Annisa Ayunda Maharani; Priyadi Nugraha Prabamukti; Anung Sugihantono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Brest care in an act of caring the breast by mothers themselves or helped by others that started from the the next day after giving birth. Breast care is an important action in breastfeeding that must be considered. Breast is an essential body organ that produces ASI which is the main food of infants aged 0-6 months. The purpose this research is to know the correlation between characteristic, knowledge and attitude of exclusive breastfeeding mom in Pegandan Health Center work area. This is a descriptive-analytic research, with cross sectional approach. The samplel of this research is 41 respondent. The result of this research showing that characteristic such as age (p=0.588), education (p=115), work status (p=0.881), parity (0.454), and knowledge (p=0.218) has no correlation with breast care behavior. And the result showing that attitude is correlated with breast care behavior (p=0.011). the conclusion is characteristic of mother and knowledge is not related with breast care behavior, and attitude is related with breast care behavior of exclusive breastfeeding mother in Pegandan Health Center work area.